Single Pd atoms synergistically manipulating charge polarization and active sites for simultaneously photocatalytic hydrogen production and oxidation of benzylamine. (May 2022) - Wang, Penglei; Fan, Shiying; Li, Xinyong; Wang, Jing; Liu, Zhiyuan; Niu, Zhaodong; Tadé, Moses O.; Liu, Shaomin
Abstract: Photocatalytic hydrogen production coupled with selective oxidation of organic substances is of significance and remains a grand challenge because of unsatisfied photocatalytic activity and unclear mechanism. Herein, we first design and synthesize atomically dispersed Pd on ZnIn2 S4 (PdSA-ZIS) for simultaneously photocatalytic hydrogen production and oxidation of benzylamine. Based on systematic characterization with a combination of theoretical simulations, light irradiation-kelvin probe force microscopy (KPFM) and time-resolved photoluminescence spectrum etc, we demonstrate that Pd single atoms can modulate charge polarization as well as the active sites of ZnIn2 S4 to promote spatial charge separation and decrease the energy barriers of reaction. The electrons are enriched around Pd single atoms-ZnS layer with lowest energy barriers of H2 production, while more holes are accumulated on InS2 layer for dehydrogenation of benzylamine. This enables PdSA-ZIS to exhibit remarkable photocatalytic performance for the co-production of N-benzylidenebenzylamine (10.2 mmol g −1 h −1 ) with selectivity of 100% and H2 (11.1 mmol g −1 h −1 ) under visible irradiation. Furthermore, by means of controlled experiments, theoretical simulations and in situ electron spin resonance (ESR) spectroscopy, a synergetic photocatalytic redox mechanism on the Pd single atom-ZIS interface for dehydrogenation and coupling of benzylamine and H2 production has been investigated in detail. Graphical Abstract: ga1 Highlights: A series of metal single-atoms loaded on ZnIn2 S4 (metal SA-ZIS) was prepared using in situ icing assisted photo-reduction method. By synergistically modulating polarization and active sites, single-atoms boost separation and transfer of photo-generated charge and reduce the energy barriers of reaction. PdSA-ZIS exhibits remarkable photocatalytic performance for the co-production of N-benzylidenebenzylamine (10.2 mmol g −1 h −1 ) and H2 (11.1 mmol g −1 h −1 ) under visible irradiation. A synergetic photocatalytic redox mechanism on the single atom-photocatalyst was revealed by theoretical simulations, light irradiation-KPFM and TRPL spectrum etc.